ROH KUDUS DALAM TRINITAS DAN KOMUNITAS UMAT TUHAN (HOLY SPIRIT IN THE TRINITY AND COMMUNITY OF GOD'S PEOPLE) - Steven Tubagus; Timotius Bakti Sarono (Widya Agape School of Theology and Indonesia Christian Theologians Association, 2021)
The doctrine of the Holy Spirit and its praxis has been controversial among God's people. This controversy has even emerged since the beginning of the church about the person and position of the Holy Spirit with God the Father and the Son. This article aims to briefly explore the doctrine of the Holy Spirit and its praxis into the community of God's people. The writing method used is a praxis systematic critical method to examine the various nuances of the argument against the Holy Spirit with the aim of placing it in a proper understanding of the trinity concept. The result of this writing is the doctrine of the Holy Spirit there is no personality difference between God the Father, the Son and the Holy Spirit, because humans meet these